2019
DOI: 10.3390/lubricants7030023
|View full text |Cite
|
Sign up to set email alerts
|

A CFD-Based Frequency Response Method Applied in the Determination of Dynamic Coefficients of Hydrodynamic Bearings. Part 1: Theory

Abstract: A general, CFD-based frequency response method for obtaining the dynamic coefficients of hydrodynamic bearings is presented. The method is grounded in experimental parameter identification methods and is verified for an extremely long, slider bearing geometry as well as short and long journal bearing geometries. The influence of temporal inertia on the dynamic response of the bearings is discussed and quantified through the inclusion of added mass coefficients within the mechanical models of the hydrodynamic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although Dousti et al [20] developed the extended Reynolds equation incorporating inertia effects, computational fluid dynamics (CFD) methods demonstrate greater efficacy in handling intricate flow physics, including inertia effects, 3D complexities, and multiphase flows. CFD methods exhibit reduced reliance on empiricism and model tuning compared to the extended Reynolds equation [21,22]. Nassab and Moayer [23] established a CFD-THD (thermohydrodynamic) lubrication model for journal bearings and found that the inertia effect would have a significant influence on the dynamic pressure lubrication of journal bearings under light loads, high speeds, and large clearances [24].…”
Section: Introductionmentioning
confidence: 99%
“…Although Dousti et al [20] developed the extended Reynolds equation incorporating inertia effects, computational fluid dynamics (CFD) methods demonstrate greater efficacy in handling intricate flow physics, including inertia effects, 3D complexities, and multiphase flows. CFD methods exhibit reduced reliance on empiricism and model tuning compared to the extended Reynolds equation [21,22]. Nassab and Moayer [23] established a CFD-THD (thermohydrodynamic) lubrication model for journal bearings and found that the inertia effect would have a significant influence on the dynamic pressure lubrication of journal bearings under light loads, high speeds, and large clearances [24].…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Dousti et al (2016), extending the classical Reynolds equations to including the inertia effect has attracted great interest in the research community. However, the CFD method more easily accommodates complex flow physics with less empiricism and model tuning (Snyder and Braun, 2018;Snyder and Braun, 2019) comparing to the extended Reynolds equation. Zhang et al (2015) provided a steady state CFD method for determining the stiffness coefficients and a simplified hydrodynamic force model can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid simulation aims to study the flow of fluid materials and has been widely applied to multiple disciplines such as chemical physics and material science [1][2][3]. However, the simulation of fluid dynamics usually requires prohibitively high computational resources [4,5] and thus limits its application in the related fields.…”
Section: Introductionmentioning
confidence: 99%